Surgical Outcomes of Robotic Resection for Sigmoid and Rectal Cancer: Analysis of 109 Patients From a Single Center in China - Peng, Jianhong; Li, Weihao; Tang, Jinghua; Li, Yuan; Li, Xueying; Wu, Xiaojun; Lu, Zhenhai; Lin, Junzhong; Pan, Zhizhong (Frontiers in Surgery, 2021)
Background: Robotic colorectal surgery has been increasingly performed in recent years. The safety and feasibility of its application has also been demonstrated worldwide. However, limited studies have presented clinical data for patients with colorectal cancer (CRC) receiving robotic surgery in China. The aim of this study is to present short-term clinical outcomes of robotic surgery and further confirm its safety and feasibility in Chinese CRC patients. Methods: The clinical data of 109 consecutive CRC patients whoreceived robotic surgery at Sun Yat-sen University Cancer Center between June 2016 and May 2019 were retrospectively reviewed. Patient characteristics,tumor traits, treatment details, complications, pathological details, and survival status were evaluated. Results: Among the 109 patients, 35 (32.1%) had sigmoid cancer, and 74 (67.9%) had rectal cancer. Thirty-seven (33.9%) patients underwent neoadjuvant chemoradiotherapy. Ten (9.2%) patients underwent sigmoidectomy, 38 (34.9%) underwent high anterior resection (HAR), 45 (41.3%) underwent low anterior resection (LAR), and 16 (14.7%) underwent abdominoperineal resection (APR). The median surgical procedure time was 270 min (range 120 - 465 min). Pathologically complete resection was achieved in all patients. There was no postoperative mortality. Complications occurred in 11 (10.1%) patients, including 3 (2.8%) anastomotic leakage, 1 (0.9%) anastomotic bleeding, 1 (0.9%) pelvic hemorrhage, 4 (3.7%) intestinal obstruction, 2 (1.8%) chylous leakage, and 1 (0.9%) delayed wound union. At a median follow-up of 17 months (range 1–37 months), 1 (0.9%) patient developed local recurrence and 5 (4.6%) developed distant metastasis, with one death due to disease progression. Conclusions: Our results suggest that robotic surgery is technically feasible and safe for Chinese CRC patients, especially for rectal cancer patients who received neoadjuvant treatment. A robotic laparoscope with large magnification showed a clear surgical space for pelvic autonomic nerve preservation in cases of mesorectal edema.